The Construction Of Resilience In The Qur’anic Perspective - Sholichatun, Yulia; Jamaluddin, Muhammad; Hikmah, Nurul; Shofia, Naila (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
This study constructs a Qur’anic Resilience Framework (QRF) by analyzing verses depicting the stories of the Prophets Ulul Azmi to reveal the psychological resilience rooted in Islamic spiritual values. Using a qualitative approach based on library research combined with focus group discussions involving experts in Qur’anic exegesis and Islamic psychology, this study develops a conceptual model of Qur’anic resilience. The main novelty lies in the integration of spiritual and cognitive dimensions—termed spiritual–cognitive resilience—which unites faith-based components (Ṣabr, Tawakkul,Riḍā, Rujā’) with reflective and adaptive actions (Al-Fikr, Al-‘Amal, Ṭsiqqah ‘Alā an-Nafs). This approach enriches modern psychological theories of resilience, which are predominantly secular, by adding a transcendental foundation grounded in tawhid. Theoretically, this research contributes to the development of Islamic psychology by presenting a conceptual framework of resilience deriving from Al-Qur'ān while reinforcing integrative methodologies between classical exegesis and empirical psychology. Practically, the findings offer implications for Al-Qur'ān-based mental health interventions, including Islamic counseling, spiritual guidance, and character education. Moreover, this study opens opportunities for developing measurement instruments and training programs on resilience grounded in Islamic spirituality, thereby strengthening the psychological well-being of Muslim communities.